2017
DOI: 10.1177/1077801216686199
|View full text |Cite
|
Sign up to set email alerts
|

Long Journeys Toward Freedom: The Relationship Between Coercive Control and Space for Action—Measurement and Emerging Evidence

Abstract: We report on the development of, and findings from, two scales measuring coercive control and space for action over a period of 3 years in a sample of 100 women who had accessed domestic violence services. We present statistical evidence to show a significant correlation between coercive control and space for action. However, dealing with violence is not a linear process, and support needs to extend beyond being enabled to separate. The scales advance measurement of women's experience of coercive control and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 10 publications
2
38
0
Order By: Relevance
“…But it contracted thereafter, as their struggles resumed, with the offending partners still at large. Sharp-Jeffs, Kelly, and Klein (2018) reported,Removing themselves from the immediate control of an abusive man was . .…”
Section: The Adaptation Of Coercive Control In Criminal Lawmentioning
confidence: 99%
“…But it contracted thereafter, as their struggles resumed, with the offending partners still at large. Sharp-Jeffs, Kelly, and Klein (2018) reported,Removing themselves from the immediate control of an abusive man was . .…”
Section: The Adaptation Of Coercive Control In Criminal Lawmentioning
confidence: 99%
“…The role of children as both a catalyst for action and a reason to endure or compromise resonates with findings from Sharp-Jeffs et al (2017). They found that, while children could be used to control women, victim-survivors often had greater space for action in the domain of parenting.…”
Section: Finance Work and Motheringmentioning
confidence: 70%
“…'Space for action' is a concept developed by Sharp-Jeffs, et al, in their 2017 article 'Long journeys toward freedom: The relationship between coercive control and space for action-measurement and emerging evidence' (building on Kelly, 2003). The 'space for action' model evaluates the ways in which the entrapment, surveillance, and restriction that are characteristic of coercive control significantly inhibit women's freedom by explicitly and implicitly curbing their behaviour (Sharp-Jeffs et al, 2017). This is of particular importance in the wake of the global COVID-19 pandemic, where the primary mechanism to prevent transmission is to create space via physical distancing.…”
Section: Introductionmentioning
confidence: 99%
“…This concept was used by Lundgren to capture how the motivations of men who are violent towards their partners are, in part, based on a desire to set limits on women's ability to exercise their freedom. The life space of women is decreased as a way of increasing the life space of the men who were violent towards them, a claim empirically tested in a recent paper by Sharp-Jeffs, Kelly, and Klein (2017). The concept was developed into the notion of space for action by Jeffner (2000) in her exploration of young people's understandings of rape, and by Kelly (2003) in relation to trafficking for sexual exploitation.…”
Section: Embodied Space For Actionmentioning
confidence: 99%